Collaborative Governance in Mangrove Ecotourism Policy on Bintan Island Coastal Approach of Penta Helix - Alfiandri Alfiandri; Bambang Irawan (Jurnal Manajemen Pelayanan Publik, 2023)
This study aims to explore the effectiveness of collaborative governance in implementing mangrove ecotourism policy on the Bintan Island coastal approach of penta helix. The research objectives are to identify the key stakeholders involved in the mangrove ecotourism policy formulation and implementation process, assess their roles and relationships, and analyze how collaborative governance can enhance their collaboration and coordination. Research method uses descriptive qualitative and uses NVivo-20 software analysis which is analyzed in depth. The results show that the penta-helix element in Collaborative Governance has gaps that do not involve all stakeholder actors, both from local government, academia, the private sector, community groups and the media. but in terms of policy or implementation of a Mangrove ecotourism program, scientific studies are needed to support Mangrove ecotourism in coastal areas in Islands Regions have strategic potential to be managed properly by strong stakeholders. The importance of active involvement of the local community as wide as possible with stakeholders such as central, regional and business actors in planning, implementing and making decisions in the formation and management of a Destination Management Organization (DMO). The findings also the need for further research to investigate can be integrated into the policy-making process and contexts.